From Amanah to Sustainability: CEO Power and ESG in Indonesia - Dina Ockta Irani; Ernie Hendrawaty; Sri Hasnawati; Adli Rikanda Saputra (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study tests whether CEO power shapes ESG performance among Indonesian infrastructure firms. We assemble a balanced panel of 24 IDX issuers (2019–2023; 120 firm-years) from Refinitiv ESG and corporate disclosures. Random-effects regressions with robust errors model ESG on CEO tenure, ownership, and duality, controlling for size, leverage, and profitability. Results show CEO tenure is positively and significantly associated with ESG, suggesting experienced yet non-entrenched leadership advances sustainability. CEO duality exhibits a positive but insignificant coefficient, while CEO ownership is negative and insignificant. Model fit is modest (R²≈0.20), implying external forces and broader governance also matter. Findings align Islamic notions of amanah and maslahah: accountable, seasoned leadership better delivers stakeholder welfare through ESG, whereas concentrated personal control does not reliably improve sustainability